Stability and Emission Characteristics of Diesel-Ethanol-Coconut Methyl Ester Blends for the Diesel Engines - Ardiyati, Tanti; Dugos, Nathaniel P.; Roces, Susan A; Suzuki, Masaaki; Kusnanto, Kusnanto (ASEAN Journal of Chemical Engineering, 2014)
The stability and emission characteristics of diesel-ethanol-coconut methyl ester (CME) blends were studied to determine the most suitable fuel blends to be applied in diesel engines. This is done in order to assess the potential of the blends as a substitute for commercially available diesel fuel used in diesel engine. The stability results of the blends using 100% and 99.5% ethanol purity showed that the fuel blends containing ethanol up to 10% and CME of 5% and greater exhibited high mutual solubility at any temperature range and were resistant to microbial growths after 3 months storage. Engine operations at low speed especially at idle-no load and using a bigger size engine lead to a minimum ignition delay and result in lower fuel consumption rate. The emission test results with the new- blended fuels showed a reduction in CO2 and increasing percentage by volume of CO2 compared to commercially available diesel. The blends could deliver an efficient combustion and could run efficiently since production of the CO2 gases is higher than that of CO. The blends of 80% diesel, 5% ethanol, 10% CME; and 80% diesel, 10% ethanol, 10% CME could reduce the smoke opacity compared to commercially available diesel.